2018
DOI: 10.1001/jamasurg.2018.1607
|View full text |Cite
|
Sign up to set email alerts
|

Association of Plane of Total Mesorectal Excision With Prognosis of Rectal Cancer

Abstract: ClinicalTrials.gov Identifier: NCT00349076.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(51 citation statements)
references
References 42 publications
3
46
0
Order By: Relevance
“…Fitzgerald et al report that in surgical treatment combined with radiotherapy, the completeness of mesorectal excision and the negative resection margin (regardless of the distance) are the most important factors for oncological outcomes [ 42 ]. Moreover, an up-to-date secondary analysis of CAO/ARO/AIO-04 trial underlines the association between the quality of mesorectal excision and the 3-year overall and disease-free survival, which is more important than the length of the margin [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fitzgerald et al report that in surgical treatment combined with radiotherapy, the completeness of mesorectal excision and the negative resection margin (regardless of the distance) are the most important factors for oncological outcomes [ 42 ]. Moreover, an up-to-date secondary analysis of CAO/ARO/AIO-04 trial underlines the association between the quality of mesorectal excision and the 3-year overall and disease-free survival, which is more important than the length of the margin [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, one of the leading topics under constant discussion is the quality of mesorectal excision. The most recent study showed an association between plane of mesorectal excision, long-term overall survival and recurrence rate [ 45 ]. In our study, there were no differences between TaTME and LaTME regarding the quality of the specimen.…”
Section: Discussionmentioning
confidence: 99%
“…In patients undergoing surgery with sphincter preservation, the three-year disease-free survival rate was higher for patients treated with TaTME than for patients treated with LapTME. These bene ts could be explained by an improved quality of the mesorectal specimen, with fewer positive resection margins, and lower rate of rectal perforations (4,22,23).…”
Section: Discussionmentioning
confidence: 99%